PHYSICAL THERAPY ACTIVITY AFTER BREAST CANCER MASTECTOMY: A LITERATURE REVIEW - Carvalho, Adrianne Moura; Salerno, Gisela Rosa Franco (Mastology, 2019)
Introduction: Breast cancer is the second most common form of cancer and the leading cause of death by cancer in women. One of the treatments is mastectomy, which brings negative physical and psychological consequences to the lives of these women, significantly reducing their quality of life. Objective: To verify the physical therapy procedures most used in the postoperative period of mastectomy. Methods: Literature review comprising articles published between 2007 and 2017, through consultation of national and international scientific papers in the following databases: Google Scholar, LILACS, MEDLINE, PubMed and SciELO, taking into account the following keywords: physiotherapy, breast cancer, mastectomy, mammoplasty, quality of life. Results: The following modalities were identified: complex decongestive therapy (CDT), manual lymphatic drainage, kinesiotherapy, low power laser, ultrasound, pneumatic compression, manual therapy, Kinesio taping and high voltage electrical stimulation. Conclusion: CDT is the most used and effective technique, however, combining several techniques results in a more complete, global and efficient treatment, showing that physical therapy is essential in all phases of treatment and significantly improves the quality of life of women that went through mastectomy.